(untitled) (The Insight, 2025)
Background: Atherosclerosis and carotid artery stenosis remain major contributors to stroke and cardiovascular morbidity and mortality worldwide, particularly among individuals over 45 years of age. The purpose of the study was to determine the prevalence of carotid stenosis and identify its associated risk factors among elderly patients. Aim of the study: To determine the prevalence and severity of carotid artery stenosis among high-risk elderly patients using Doppler ultrasonography. Methods & Materials: This descriptive cross-sectional study was conducted from September 2012 to February 2013 in the Department of Medicine, Department of Vascular Surgery, and the Institute of Nuclear Medicine and Ultrasound at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. A total of 100 elderly patients (>55 years) with one or more risk factors (hypertension, diabetes mellitus, dyslipidemia, or family history of stroke) were selected by convenient sampling. Patients aged <55 years, with carotid aneurysms or congenital anomalies, or unwilling to consent were excluded. Carotid stenosis was defined as ≥50% arterial narrowing (moderate) and ≥70% (severe). Data were collected via structured interviews, clinical examination, and investigations, then analyzed using SPSS with results expressed as mean ± SD or percentages; p < 0.05 was considered significant. Ethical approval was obtained, and informed consent was secured from all participants. Results: Among 100 elderly patients (mean age 65.6 ± 8.1 years; 64% males), 73% had carotid stenosis (mild 60%, moderate 7%, severe 6%). Most were sedentary (89%), exercised occasionally (96%), and 63% were smokers. Hypertension (64%), dyslipidemia (58%), ischemic heart disease (42%), and TIA (39%) were common. Significant associations with stenosis were found for hypertension (70% vs 48%, p = 0.04), dyslipidemia (48% vs 26%, p = 0.04), ischemic heart disease (49% vs 22%, p = 0.01), and TIA (45% vs 22%, p = 0.03); diabetes/IGT was not significant. Conclusion: Carotid artery stenosis was highly prevalent among high-risk elderly patients, predominantly mild in severity, and showed significant associations with hypertension, dyslipidemia, ischemic heart disease, and transient ischemic attack.